Análisis comparativo entre distribuciones de software libre orientadas a la ciberseguridad usando técnicas de pentesting y herramientas de hacking ético aplicadas a la red de la Escuela de Educación Básica San Felipe Neri. - Pilco Cando, Bayron Edison (2023)
The main purpose of this research study was to focus on information security. Information is the most precious resource that a person or company possesses, which is why the security required to maintain its confidentiality, integrity, and availability will depend on how advanced it is concerning cyber security, more specifically the analysis of vulnerabilities that the information system may have. This paper details the stages of a computer audit with the implementation of applications and tools used to discover possible vulnerabilities within the network of the Escuela de Educación Básica San Felipe Neri, through reports that compare the results obtained by two free software distributions oriented to ethical hacking and pen testing. In addition to this, it is proposed to apply a security protocol that could help mitigate a vulnerability, with emphasis on the use of an exploit, which is a script with commands that can prevent the vulnerability from being exploited for malicious purposes and impact its information system